2018
DOI: 10.3340/jkns.2017.0252
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Spinal Distribution of Cy5.5 Fluorescent Dye after Injection via the Lateral Ventricle and Cisterna Magna in Rat Model

Abstract: ObjectiveThe purpose of this study was to find an optimal delivery route for clinical trials of intrathecal cell therapy for spinal cord injury in preclinical stage.MethodsWe compared in vivo distribution of Cy5.5 fluorescent dye in the spinal cord region at various time points utilizing in vivo optical imaging techniques, which was injected into the lateral ventricle (LV) or cisterna magna (CM) of rats.ResultsAlthough CM locates nearer to the spinal cord than the LV, significantly higher signal of Cy5.5 was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…2l, m and Supplementary Table 1 ). Similar to previous studies examining differences in spinal CSF tracer distribution following intraventricular vs. ICM injection 44 , we did not see substantial amounts of tracer in the thoracic or lumbar spine following injection into the cisterna magna.…”
Section: Resultssupporting
confidence: 90%
“…2l, m and Supplementary Table 1 ). Similar to previous studies examining differences in spinal CSF tracer distribution following intraventricular vs. ICM injection 44 , we did not see substantial amounts of tracer in the thoracic or lumbar spine following injection into the cisterna magna.…”
Section: Resultssupporting
confidence: 90%
“…Our results are consistent with previous reports. In a previous study, we have injected Cy5.5 fluorescent dye into LV or cisterna magna of rats without SCI and found that LV injection is suitable for the delivery of Cy5.5 fluorescent dye to spinal cords by the CSF circulation [ 11 ]. In this study, we further demonstrate that LV injection is adequate for the distribution of soluble Cy5.5 fluorescent dye and colloidal FMNP-labelled U87MG cells in the entire spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, intrathecal injection of stem cells has been considered in clinical trials, expecting stem cells to migrate into disease sites via cerebrospinal fluid (CSF) [ 8 10 ]. To simulating clinical situation in animal models, we have injected Cy5.5 fluorescent dye into the lateral ventricle (LV) or cisterna magna (CM) of rat without SCI and compared its in vivo distribution in each region of spinal cord [ 11 ]. LV injection is more suitable than CM injection since it induces widespread distribution of Cy5.5 in spinal cords [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Özellikle floresan nanopartiküllerin gelecekte daha yaygın olarak in vivo izlemelerde kullanılacakları öngörülmektedir. Lee at al [39] Niad-4 475-480 625-650 Β-amiloid İn vivo çalışmaya uygun Rao et al [15] Bae et al [40] Tokyo green 491 510 Hidrofobik,…”
Section: Floresan ışıMaya Dayalı Görüntüleme Tekniklerinin Avantajlarunclassified